(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
Tambourine musical instrument is a musical instrument that can be easily found in Indonesia. Tambourine musical instrument is generally used in Melayu music and also in Qosidah accompaniment. The tambourine is one of the musical instruments that can be associated with mathematics, especially geometry. The purpose of this research is to find out the geometric elements contained in the Tambourine Hadroh musical instrument and to find out the implementation of using the Geogebra application to determine the area and volume of Rebana Hadroh’s rotating object. The method used in this research is a literature study and data collection will be carried out by conducting experiments on the GeoGebra application. Through this research, it was found that the area of Rebana Hadroh was 663.12 area units and the volume of the rotating object was 12, 739.75 volume units.